The development of a method for the detection and estimation of CCHF virus RNA in tick species - Du Preez, Patrick Hendrik (University of the Free State, 2000)
Crimean Congo haemorrhagic fever (CCHF), caused by a RNA virus, is a tick-borne viral zoonosis occurring in Europe, Asia and Africa. The fatality rate is ±30%. Rapid and accurate diagnosis is essential. The aim of this study was to develop a reverse transcription-polymerase chain reaction (RT-PCR) with internal control for the detection of CCHF RNA. Primers were selected for a region in the nucleocapsid - gene of the S segment. The internal control was constructed by ligating this PCR product into a pGEMEX-1 vector. Sequencing of the PCR product (381 bp) revealed two unique restriction sites, BIn I and BstE II which were used to delete a fragment of 59 bp. The shortened PCR-product was re-inserted into E. coli. T3 RNA polymerase produced plasmid derived RNA (322 bp) was used to spike specimens. Standard RT-PCR was then performed. The minimum concentration of target RNA the RTPCR can detect was estimated to be 4 x 10-5 pmol RNA, giving more or less the same sensitivity as the PCR alone. The size difference of 59 bp is enough to distinguish between the full-length and the deletion variant inserts when visualised and therefore provides an internal control. RT-PCR on fifty Hyalomma ticks was negative. The CCHF virus was probably not present or at concentrations below detection level, as RT-PCR of control CCHF virus RNA confirmed the accuracy of the method. RT-PCR allows rapid detection of CCHF virus RNA. The constructed internal control precludes the use of Dugbe virus, an antigenically related nairovirus.
Dissertation (M.Med.Sc. (Medical Microbiology and Virology))--University of the Free State, 2000
Keywords: Hemorrhagic fever; Virus diseases; Communicable diseases -- South Africa